Karakteristik Klinis Pasien Demam Tifoid di RSUP Sanglah Periode Waktu Juli 2013 – Juli 2014 - Adiputra, I Komang Gede Triana; Somia, I Ketut Agus (E-Jurnal Medika Udayana; Vol 6 No 11 (2017): E-Jurnal Medika Udayana, 2017)
Typhoid fever remains a challenge for the clinician in the tropics because the symptoms are not typical and need appropriate tests in the diagnosis of this case. The purpose of this research is to describe the clinical characteristics of typhoid fever in patients who come to Sanglah on July 2013 - July 2014. This research method using descriptive observational study and using cross-sectional approach, total sampling technique by using secondary data on the patient’s medical record at Medical Record Installation Sanglah on July 2013 - July 2014 which positively diagnosed with typhoid fever. The results showed 50 samples, which consisted of 25 male patients and 25 female patients. Overview of the clinical characteristics of patients with typhoid fever in Sanglah are the main complaint and signs and symptoms that often arises is fever in all patients. For laboratory tests tend to show thrombocytopenia (36%), mild anemia (34%), and leukopenia (26%), while the widal test Typhi Typhi H and O show a negative value. For the examination of IgM anti-salmonella 6 is the largest value that is in 7 patients (43.8%). As for the examination of SGOT and SGPT tend to show improvement. Result show the patient’s condition tends to improve after given antibiotics and only 1 patient with complications of hepatitis tifosa. It can be concluded that the clinical characteristics of patients with typhoid fever in Sanglah tend to show similarities with previous studies, although some variables show a different percentage with previous research. Keyword: typhoid fever, characteristics, secondary data